Kebijaksanaan dan Pengaruhnya Terhadap Kinerja Perusahaan Industri Fotografi di Kota Bandar Lampung - Muhiddin Sirat; Imam Awaluddin; Shandi Farizki (Jurnal Ekonomi Pembangunan, 2019)
This study aims to analyze the market structure and application of company policies in the photography industry in Bandar Lampung City and their effects on business performance. The first analytical tool used is the Herfindahl Index and Market Share to measure the market structure. Second, correlation analysis to measure the relationship between market structure and the achievement of targets for the implementation of company policy. Finally, multiple linear regression analysis to measure the effect of the target achievement of the implementation of company policy on business performance. The results showed that: (1). The structure of the photography industry market in Bandar Lampung City is a monopolistic competition market with a Herfindahl Index = 0.06103 approaching 0; (2). The market structure has a low correlation with the achievement of the target of applying price policy Rxy <0.5), and (3). The achievement target of the implementation of company policy (price policy, product policy, marketing and promotion policy, service policy to consumers) has a significant positive effect on business performance.